Global polarization of Λ and Λ[bar] hyperons in Au+Au collisions at √sNN=19.6 and 27 GeV - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2023)
In relativistic heavy-ion collisions, a global spin polarization, PH, of Λ and Λ[bar] hyperons along the direction of the system angular momentum was discovered and measured across a broad range of collision energies and demonstrated a trend of increasing PH with decreasing √sNN. A splitting between Λ and Λ[bar] polarization may be possible due to their different magnetic moments in a late-stage magnetic field sustained by the quark-gluon plasma which is formed in the collision. The results presented in this study find no significant splitting at the collision energies of √sNN=19.6 and 27 GeV in the BNL Relativistic Heavy Ion Collisions Beam Energy Scan Phase II using the STAR detector, with an upper limit of PΛ[bar]−PΛ<0.24% and PΛ[bar]−PΛ<0.35%, respectively, at a 95% confidence level. We derive an upper limit on the naive extraction of the late-stage magnetic field of B<9.4×1012 T and B<1.4×1013 T at √sNN=19.6 and 27 GeV, respectively, although more thorough derivations are needed. Differential measurements of PH were performed with respect to collision centrality, transverse momentum, and rapidity. With our current acceptance of |y|<1 and uncertainties, we observe no dependence on transverse momentum and rapidity in this analysis. These results challenge multiple existing model calculations following a variety of different assumptions which have each predicted a strong dependence on rapidity in this collision-energy range.
*STAR Collaboration: M.I. Abdulhamid, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [und 370 weitere Personen]
Im Titel steht der zweite Buchstabe Lambda mit einem Oberstrich
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 30.01.2024